Analisis Kualitas Udara Indoor di Ruang Rawat Inap Rumah Sakit Budi Agung Kota Palu - Priescilla Arlyani; Budiman Budiman; Hamidah Hamidah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Indoor air quality in inpatient wards constitutes a critical dimension of hospital environmental health, as it directly intersects with patient comfort, occupational safety for health personnel, and the prevention of healthcare associated infections. This study aimed to evaluate the physical air environmental quality of inpatient rooms at Budi Agung Hospital using selected environmental health parameters. A descriptive observational design with a cross sectional approach was employed. Data were obtained through direct measurements of air temperature, relative humidity, air flow velocity, lighting intensity, noise level, PM 2,5 concentration, PM 10 concentration, and airborne bacterial count. Physical air parameters were measured at 71 observation points, while airborne bacterial counts were assessed before and during patient visiting hours. The findings demonstrate that air temperature, relative humidity, and air flow velocity were the principal parameters that failed to comply with the required environmental health standards. Only 1 of 71 temperature measurement points met the standard, whereas 70 points did not. For relative humidity, 55 of 71 points failed to meet the standard, while for air flow velocity, 61 of 71 points were non compliant. Lighting intensity showed a more favorable profile, with 66 of 71 measurement points meeting the required standard. Noise level, PM 2,5 concentration, and PM 10 concentration met the standards across all measurement points. Airborne bacterial counts also remained within the acceptable standard in all examined rooms, although higher counts were observed during patient visiting hours compared with the period before visiting hours. These findings indicate that the physical air environment of inpatient rooms requires targeted improvement, particularly in the regulation of air temperature, relative humidity, and air flow velocity. Strengthening routine environmental monitoring, optimizing ventilation performance, ensuring scheduled maintenance of air conditioning systems, and controlling visitor density are necessary to establish a safer, more comfortable, and healthier inpatient care environment.